1997
DOI: 10.1002/(sici)1096-9071(199709)53:1<4::aid-jmv2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herpes simplex virus on the DNA of human papillomavirus 18

Abstract: Some types of human papillomaviruses (HPV) appear to be associated with carcinoma of the cervix or other tissues, but patients infected with HPV do not necessarily develop carcinoma. Some epidemiological studies of risk factors for cervical carcinoma have indicated the involvement of herpes simplex virus (HSV). To study the effect of HSV on the genome of HPV, total DNAs were extracted and analyzed after HeLa cells, or A431 cells, transiently transfected with HPV18 DNA, were infected with HSV-1 or -2 for 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In vitro studies have shown, that HSV and HPV tolerate well each other, even enhance each other's growth and may play a synergistic role in oral carcinogenesis. 21,35,36 However, the numbers in the present study are too few to draw any further conclusions and more studies are needed. No HPV co-infections with HSV-2 or CMV were found.In our study, HPV was found in 76% in the oral cancers, which is a higher number than the recent meta-analysis have shown.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown, that HSV and HPV tolerate well each other, even enhance each other's growth and may play a synergistic role in oral carcinogenesis. 21,35,36 However, the numbers in the present study are too few to draw any further conclusions and more studies are needed. No HPV co-infections with HSV-2 or CMV were found.In our study, HPV was found in 76% in the oral cancers, which is a higher number than the recent meta-analysis have shown.…”
Section: Discussionmentioning
confidence: 99%
“…Oral HPV infection in individuals with and without HIV infection was associated with HSV-2 seropositivity, an accepted surrogate measurement of several sexual behaviors [27]. Recently, HSV-2 infection was demonstrated to increase the risk of an incident HPV infection [32], and it has been suggested that HSV-2 may act to promote cervical disease progression [33][34][35], even though HSV-2 sequences have not been found in tumors [36]. In the present study, however, oral HPV infection was significantly associated with seroreactivity to HSV-2 but not with HSV-1, the herpes virus that more commonly infects the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed possible that functions of HSV-1 might be having a direct or indirect effect on activity of URR16. HSV has been reported to increase 31 or to suppress 32,33 the activities of different papillomaviruses, and cloned fragments of HSV-1 have been shown to activate the URR of HPV-16 in some cells. 34 In oral cancer cells that had been transfected with the URR-luciferase reporter plasmid, expression was increased by up to 30-fold when the cells were infected with HSV-1 ( Figure 9).…”
Section: Discussionmentioning
confidence: 99%